"We're Going Under": The Role of Local News Media in Dislocating Climate Change Adaptation. Issue 5 (4th July 2021) - Bowden, Vanessa; Nyberg, Daniel; Wright, Christopher
ABSTRACT: As carbon emissions continue to rise, the need to adapt to climate impacts has become increasingly urgent. Planning and implementing climate adaptation is often left to local authorities and is fraught with the challenge of negotiating with multiple stakeholders holding differing interpretations of climate change. In such a space, local media has a critical role in communicating these differing perspectives within communities. In this article we explore the central role of a local newspaper in shaping public debate over the implementation of a climate adaptation plan in a coastal region of Australia. Rather than providing an arena for public discussion and constructive debate, we find that the newspaper adopted a clear position rejecting the need for changes in planning for anticipated climate impacts. We use the case study to explore how media discourse contributes to (i) the construction of an antagonistic debate undermining climate science, and (ii) strengthening the hegemony of economic value and property rights. In response, we suggest shoring up political alliances for climate change, including in the local media, as a basis for social change.